Dekonstruksi Inspiration Porn: Analisis Wacana Kritis Model Van Dijk terhadap Representasi ABK Berdaya Ekonomi pada Instagram - Nazharullah, Ridha; Fadilah, Haris; Shapiah, Shapiah; Putri, Lisya Ramitha (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to deconstruct the phenomenon of inspiration porn through the representation of Children with Special Needs (ABK) on the Instagram account @abk.umkm.indonesia. The primary issue addressed is the ethical ambiguity in sharenting practices and the potential for disability commodification within digital spaces. The research utilizes Teun A. van Dijk's Critical Discourse Analysis (CDA) with a qualitative-interpretative approach. The multimodal data consists of caption texts, visual video elements, and audio narratives. A purposive sampling technique was applied, selecting all 145 posts from January 2024 to January 2026 that achieved above-average interaction rates. Data collection was conducted through digital documentation, text scrapping, video transcription, and passive participant observation. Findings reveal a paradigm shift in representation from "pity objects" to empowered "economic agents". Textually, the account consistently employs empowerment diction and professional visualizations to highlight creative potential . Cognitively, the account managers demonstrate a conscious effort to break the stigma by emphasizing the commercial value of the children's work. In a social context, this practice serves as a resistance discourse against systemic ableism. However, a paradox of positive commodification remains, where disability identity is utilized as a Unique Selling Point (USP) to capture algorithmic attention. This study concludes that while the account successfully re-brands disability identity, it still leaves a challenge regarding conditional social acceptance, which requires individuals with special needs to constantly appear productive.